Fluid replacement via the rectum for treatment of hypovolaemic shock in an animal model. Issue 11 (20th October 2006) - Girisgin, A S; Acar, F; Cander, B; Gul, M; Kocak, S; Bodur, S
Abstract : Background: The importance of early and effective fluid resuscitation in hypovolaemic shock treatment is indisputable. Aim: To examine the effects of fluid replacement via the rectum in an animal model of hypovolaemic shock as a possible life-saving method in situations where veins cannot be accessed quickly. Methods: Rabbits were randomly divided into two groups: a control group of 7 animals and a second group of 10, the fluid replacement via the rectum (FRVR) group. The femoral artery of each subject was catheterised and 15 ml blood was withdrawn over 1 min at 5-min intervals. After reaching a mean arterial pressure (MAP) of 30 mm Hg, additional blood was withdrawn until the MAP dropped to <25 mm Hg, at which time blood withdrawal ceased. At this point, control animals were given no treatment and were monitored for 30 min. The FRVR group, however, was given 0.9% sodium chloride solution (amount equal to three times the amount of blood withdrawn) via the rectum over a 15-min period. The MAPs of both groups were then measured, every 5 min after the start of resuscitation, for 30 min. Results: In the FRVR group, the MAP began to rise significantly after 15 min of receiving fluid per rectum (p = 0.035) and continued to be significantly greater than the control group at 20, 25 and 30 min (p = 0.035, 0.002 and 0.001, respectively). Conclusion: FRVR is a viable alternative for fluid resuscitation in this animal model of hypovolaemic shock. This easy and non-invasive method of fluid replacement may be useful when standard intravenous access is unobtainable, and should be compared with other access routes using varying types and amounts of fluids in future animal studies.